Perspektif Hukum Keluarga Islam Mensikapi Dampak Revolusi Indusri 4.0 - Nur Rofiq; Khoiruddin Nasution; Umdatul Baroroh; Rahmawati Rahmawati; Nashih Muhammad (Jurnal Iqtisad, 2023)
The Industrial Revolution 4.0 has a wide range of effects on people's lives and posed a challenge for families. The goal of this research is to examine the relationship between family law and the 4.0 industrial revolution, as well as the Islamic family's reaction to the impact, the function of the family, and methods to defend the family in the face with it. This type of library study was conducted using a descriptive-qualitative technique. The study's findings indicate that the relationship between family law and the Industrial Revolution 4.0 is very close, particularly in terms of moving the wheels of the economy, and that it has a favorable impact on those who know how to use it correctly. Create a detrimental influence on people who are lulled into abusing it. The effects on the family include family emphasis centered on pursuing pleasure, a lack of parental attention, excessive use of devices, the disintegration of a full family system, and materialistic existence. The family's role in mitigating the effects of the Industrial Revolution 4.0 is to apply moral values, specifically: religious function, reproductive function, socio-cultural function, protection function, love and compassion function, economic function, socialization and education function, and environmental function. Families must also be able to establish norms and cultural standards, as well as cultivate media and information literacy and create democratic family communication patterns. While the solution is to promote a mutual understanding attitude, role actualization, reward presentation, good and effective communication, instilling positive discipline, and developing a quality generation.